English as a Medium of Instruction for Islamic Higher Education: Classroom Pedagogy, Students' Motivation, and Challenges - Agus Husein As Sabiq; Desi Wijayanti Ma'rufah; Ana Mae M. Monteza (Yayasan Keluarga Guru Mandiri, 2025)
Indonesian Islamic universities have conducted little research on English as a medium of instruction (EMI) for Islamic education students. Thus, this study explored EMI pedagogy for Islamic education. This study also examined student motivation and learning obstacles. Five lecturers and 128 students in three classrooms from different Islamic Education Department year levels at a State Islamic University in Indonesia have been investigated using qualitative observation and semi-structured interviews. The Transitional Bilingual Observation Protocol (TBOP) was used for observation results and thematic analysis for interview outcomes. Lecturers spent more time on lecturing, small group discussions, and presentations. The 2nd-semester lecturers employed translanguaging strategies for communication, while the others used the primary language and English with some mistakes. Students' desire to enhance their English was why they joined a bilingual program. Most students are excited to join EMI courses, but many struggle to communicate in English during class owing to concerns about making mistakes and speaking insecurely. Additionally, lecturers' English communication skills are limited during English education. This research shows that the institution should improve professors' communicative skills and students' language skills rather than only marketing multilingual classes.